Dry needling in the management of myofascial trigger points: A systematic review of randomized controlled trials. (August 2017) - Espejo-Antúnez, Luis; Tejeda, Jaime Fernández-Huertas; Albornoz-Cabello, Manuel; Rodríguez-Mansilla, Juan; de la Cruz-Torres, Blanca; Ribeiro, Fernando; Silva, Anabela G.
Highlights: Dry needling can be cautiously recommended to improve pain and range of motion in the neck and shoulder in the short term. There is insufficient evidence on dry needling effectiveness for pain and range of motion in the long-term. There is insufficient evidence on dry needling effectiveness, both in the short and long term, for disability, analgesic medication intakeand sleep. There is a need to standardize and fully describe the application of dry needling. Abstract: Objective: This systematic review of randomized controlled trials aimed to examine the effectiveness of dry needling in the treatment of myofascial trigger points and to explore the impact of specific aspects of the technique on its effectiveness. Methods: Relevant studies published between 2000 and 2015 were identified by searching PubMed, Scopus, The Cochrane Library and Physiotherapy Evidence Database. Studies identified by electronic searches were screened against a set of pre-defined inclusion criteria. Results: Fifteen studies were included in this systematic review. The main outcomes that were measured were pain, range of motion, disability, depression and quality of life. The results suggest that dry needling is effective in the short term for pain relief, increase range of motion and improve quality of life when compared to no intervention/sham/placebo. There is insufficient evidence on its effect on disability, analgesic medication intake and sleep quality. Conclusions: Despite some evidence for a positive effect in the short term, further randomized clinical trials of high methodological quality, using standardized procedures for the application of dry needling are needed.